Measurement of differential cross sections for Higgs boson production in the diphoton decay channel in pp collisions at $\sqrt{s}=8\,\text {TeV} $ - CMS collaboration (2314 authors) (2016)
A measurement is presented of differential cross sections for Higgs boson (H) production in pp collisions at $\sqrt{s}=8$ $\,\text {TeV}$ . The analysis exploits the ${H} → {γ }{γ }$ decay in data corresponding to an integrated luminosity of 19.7 $\,\text {fb}^\text {-1}$ collected by the CMS experiment at the LHC. The cross section is measured as a function of the kinematic properties of the diphoton system and of the associated jets. Results corrected for detector effects are compared with predictions at next-to-leading order and next-to-next-to-leading order in perturbative quantum chromodynamics, as well as with predictions beyond the standard model. For isolated photons with pseudorapidities $|η |<2.5$ , and with the photon of largest and next-to-largest transverse momentum ( $p_{T} ^{γ }$ ) divided by the diphoton mass $m_{γ γ }$ satisfying the respective conditions of $p_{T} ^{γ }/m_{γ γ }> 1/3$ and ${>}1/4$ , the total fiducial cross section is $32 ± 10$ $\text {\,fb}$ .